Integration of Information and Communication Technologies (ICT) on Pupils’ Learning of English in Selected Schools in Buyanja Town Council, Rukungiri District. - Arinaitwe, Frankline (Kabale University, 2025)
The topic of the study was on the he integration of information and communication technologies (ICT) on pupils’ learning of English in selected schools in Buyanja Town Council, Rukungiri district. The study was guided by the three objectives: To find out the role of integrating information and communication technologies (ICT) on pupils’ learning of English in selected schools, to investigate the factors hindering the effective integration of ICT in pupils' learning of English in selected schools, to explore strategies employed to overcome challenges hindering the effective integration of ICT in pupils' learning of English in Buyanja Town Council, Rukungiri district. Literature was reviewed according to the above objectives. The study used a descriptive cross- sectional study. A cross-sectional design was a type of observational study, or descriptive research that involved analyzing information about a population at a specific point in time. The study took a total of 50 respondents that is each school the researcher selected 5 pupils, 4 teachers and 1 head teacher by use of simple random sampling and purposive sampling. Data from quantitative and qualitative research was then analysed and presented in form of tables and graphs. Conclusions, recommendations suggestions for further research studies were finally made.